Flour blast test demonstrator - ZHU WANJING (2015)
The utility model relates to the teaching testing tool technical field, and discloses a flour blast test demonstrator comprising an iron frame, an upper bottle and a lower bottle; the upper and lower bottles are made of waste drink bottles with different inner diameters, and bottoms of the bottles are cut off so as to be inverted for buckling; a bottle neck if the upper bottle is sealed, a bottle neck of the lower bottle is provided with a cork; the cork is inserted by a guide pipe and a combustion spoon; a top of the combustion spoon is arranged in a cavity of the lower bottle and provided with a candle; one end of the guide pipe extends into the cavity of the lower bottle, and the other end of the pipe is connected with an inflator through a soft pipe. The container formed by the upper and lower bottles is large in capacitor, sufficient in oxygen, so the candle cannot be extinguished when the container is inflated, thus prolonging a candle combustion time; an inflator can inflate with large air flow, and rising flour can easily reach a lower limit concentration for explosion, and test success rate is high; waste drink bottles are employed, a flour blast test whole process can be clearly and completely presented, and the demonstrator is convenient in observation, and high in safety factors.